COMMUNITY PARTICIPATION AND SUSTAINABLE EDUCATIONAL INFRASTRUCTURE IN RURAL NIGER STATE - LAKAN, MOHAMMED JIYA (Sokoto Educational Review, 2025)
Sustainable educational infrastructure in rural Niger State presents a significant developmental challenge. Despite governmental efforts, many communities still lack basic educational facilities due to funding limitations, policy gaps, and insufficient stakeholder engagement. This study investigated the role of community participation in fostering the sustainable development of educational infrastructure in rural areas of Niger State. Using a quantitative method, data were collected from 349 respondents, including community leaders, school heads, parents, and government officials, across nine selected rural communities in Niger State: Kontagora, Magama, Wushishi (Zone A); Chanchaga, Paikoro, Bosso (Zone B); and Lapai, Agaie, Katcha (Zone C). A multistage sampling technique was employed, and the sample size was determined using the Taro Yamane formula. Data were collected via a structured questionnaire designed on a 5-point Likert scale and analyzed using descriptive statistics (frequency counts, percentages, means, and standard deviations) in SPSS Version 25. The findings revealed that community involvement in the planning, construction, and maintenance of school infrastructure significantly influenced the sustainability of such projects. In communities where resources—such as labor, land, and local materials—were contributed, projects exhibited higher levels of maintenance and utilization. DOI: https://doie.org/10.10318/SER.2025195173